Do children with autism 'switch off' to speech sounds? An investigation using event-related potentials. - Whitehouse, A; Bishop, D (2008)
Autism is a disorder characterized by a core impairment in social behaviour. A prominent component of this social deficit is poor orienting to speech. It is unclear whether this deficit involves an impairment in allocating attention to speech sounds, or a sensory impairment in processing phonetic information. In this study, event-related potentials of 15 children with high functioning autism (mean nonverbal IQ = 109.87) and 15 typically developing children (mean nonverbal IQ = 115.73) were recorded in response to sounds in two oddball conditions. Participants heard two stimulus types: vowels and complex tones. In each condition, repetitive 'standard' sounds (condition 1: vowel; condition 2: complex tone) were replaced by a within stimulus-type 'deviant' sound and a between stimulus-type 'novel' sound. Participants' level of attention was also varied between conditions. Children with autism had significantly diminished obligatory components in response to the repetitive speech sound, but not to the repetitive nonspeech sound. This difference disappeared when participants were required to allocate attention to the sound stream. Furthermore, the children with autism showed reduced orienting to novel tones presented in a sequence of speech sounds, but not to novel speech sounds presented in a sequence of tones. These findings indicate that high functioning children with autism can allocate attention to novel speech sounds. However, they use top-down inhibition to attenuate responses to repeated streams of speech. This suggests that problems with speech processing in this population involve efferent pathways.